Who is a refugee? a philosophical account - Oteng, Onalethata (Rhodes University, Faculty of Humanities, Department of Philosophy, 2019)
This thesis comprises two sections: the first section considers who is a refugee and who is not a refugee; and the second section illustrates the necessity of amending the present international laws and conventions to include other people who should also be recognised as refugees. The critical issue regarding the definition of a refugee, is whether or not there is adequate evidence concerning the current understanding of the notion of who a refugee is. Therefore, in order to reach these goals, this thesis is divided into five chapters. The first chapter explores the definitions pertaining to what it means to be a refugee. The second chapter takes into account the different types of victims that are excluded from the notion of refugee. The third chapter considers the consequences of having a restricted understanding who qualifies to be a refugee. The fourth chapter provides alternative solutions that would assist in providing a more comprehensive definition. Furthermore, chapter five discusses the necessity to further expand the refugee concept to include other forms of victims that are not already included. Overall, this thesis seeks to support expansion of the term 'refugee' since the reasons for forced migration have changed, and individuals are not only fleeing from individual persecution, for instance, but from other situations that can be considered to fall under forced migration. Consequently, extending the definition of the term 'refugee' should occur, because refusing to consider revising the term amounts to a refusal to show acceptance and empathy to today's other migrants who are also experiencing survival challenges in their home countries.
Keywords: Refugees -- Philosophy; Refugees -- Government policy; Refugees -- Legal status, laws, etc.; United Nations Conference of Plenipotentiaries on the Status of Refugees and Stateless Persons (1951 : Geneva, Switzerland)